RANCANG BANGUN SISTEM PEMESANAN LAPANGAN FUTSAL BERBASIS WEB MOBILE - Setiawan, Dwi; Yulianton, Heribertus (Information Technology and Telematics, 2018)
Abstract- In order to make futsal field booking system that is applied at this time, make customer less take time, besides customer also still difficulties in getting information about field usage schedule and event which will be held in futsal field. With the development of technology, futsal rental system online intends to utilize the media website as one way to get closer to the customer and make it easier for customers to make reservations and get information.System development method used in this research is Waterfall which consist of system start, system analysis, system design using UML, system implementation using PHP and MySQL.The end result of this research is a mobile web based futsal ordering system can be used to manage the recording of futsal field booking online on Alex Futsal Porwodadi and can be used to display events related to futsal